Network model and topology control algorithm based on hierarchical autonomous system in space information network - Wei ZHANG; Geng-xin ZHANG; Dong-ming BIAN; Liang GOU; Zhi-dong XIE (Tongxin xuebao)
Due to the distinguishing characteristics of space information network (SIN) such as large scale,high component complexity and dynamic,a novel network model based on hierarchical autonomous system (AS) was proposed.This model divided the complex SIN into simpler AS and sub-AS networks according to node properties,link capabilities,task features,distribution areas,etc.In these AS or sub-AS networks,different control strategies could be adopted.In this way,the dynamic network was decoupled into semi-static sub-networks,and the high dynamic coupling problem among sub-networks was solved.Then,an AS network topology control algorithm based on the hierarchical autonomous system model was proposed to minimize the time delay in the SIN.Compared with most existing approaches for SIN where either the purely centralized or the purely distributed control method was adopted,the proposed algorithm was a hybrid control method.In order to reduce the cost of control,the control message exchange was constrained among neighboring sub-AS networks.It is proved that the proposed algorithm achieve logical k-connectivity on the condition that the original physical topology is k-connectivity.Simulation results validate the theoretical analysis and effectiveness of the algorithm.